The Influence of Mindfulness and Social Connectedness in Strengthening Job Embeddedness through Sustainable Well-Being as a Mediator Variable at Industrial Estate Area - Bekasi Regency - Ninik Anggraini; Wardani Rahayu; Corry Yohana (IJHCM (International Journal of Human Capital Management), 2023)
Background: This research aims to identify of Mindfulness, social connectedness and Sustainable Well-Being as intervening variable to strengthen Job Embeddedness Research Method: This study adopted a quantitative approach and collected data from 197 respondents and used random sampling. In this study the proposed model uses a structural equation model with assisted data processing using Smart-PLS software. Results and Conclusion: Sustainable well-being is only influenced by mindfulness and social connectedness. Others variable do not have an impact not only on sustainable well-being, but also on job embeddedness. Mindfulness and social connectedness also do not have a direct effect on job embeddedness but are mediated through the role of sustainable well-being.